2015
DOI: 10.1007/s00330-015-3920-z
|View full text |Cite
|
Sign up to set email alerts
|

Isometric stress in cardiovascular magnetic resonance—a simple and easily replicable method of assessing cardiovascular differences not apparent at rest

Abstract: • Isometric exercise unmasks cardiovascular differences not evident at rest. • CMR is the reference standard for non-invasive cardiovascular assessment at rest. • A new easily replicable method combines isometric exercise with CMR. • Significant haemodynamic changes occur and differences are unmasked. • The physiological, isometric CMR stressor can be easily replicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Overweight subjects showed less increase in heart rate and cardiac output [52]. This is in accordance with a study done in 75 healthy volunteers (age 38.8 ± 10.9 years) that examined the effects of biceps isometric exercise and found that BMI is associated with reduced augmentation of the CO [35]. Isometric handgrip exercise during cMRI can also be used to examine coronary endothelial function (CEF) [59, 61, 62, 67, 86, BP blood pressure, BPM beats per minute, SBP systolic blood pressure, DBP diastolic blood pressure, HR heart rate, MAP mean arterial pressure, MVC maximum voluntary contraction, ΔHR difference in heart rate between rest and exercise, ΔMAP difference in mean arterial pressure between rest and exercise 87, 89-91, 93, 95, 104-106].…”
Section: Isometric Handgrip Exercise and The Effects On Cardiac Adaptsupporting
confidence: 89%
See 2 more Smart Citations
“…Overweight subjects showed less increase in heart rate and cardiac output [52]. This is in accordance with a study done in 75 healthy volunteers (age 38.8 ± 10.9 years) that examined the effects of biceps isometric exercise and found that BMI is associated with reduced augmentation of the CO [35]. Isometric handgrip exercise during cMRI can also be used to examine coronary endothelial function (CEF) [59, 61, 62, 67, 86, BP blood pressure, BPM beats per minute, SBP systolic blood pressure, DBP diastolic blood pressure, HR heart rate, MAP mean arterial pressure, MVC maximum voluntary contraction, ΔHR difference in heart rate between rest and exercise, ΔMAP difference in mean arterial pressure between rest and exercise 87, 89-91, 93, 95, 104-106].…”
Section: Isometric Handgrip Exercise and The Effects On Cardiac Adaptsupporting
confidence: 89%
“…Adaptations to physical exercise may not only be impaired in clinical populations with known Figure of the cardiovascular stress response, focusing on the main effects in the exercising muscles, brain and the cardiovascular system cardiovascular or cardiac disease. Already, when subtle subclinical differences in cardiovascular health are present, this may lead to suboptimal adaptions of the cardiovascular system to the increased demands induced by exercise [34,35]. Thus, measurement of the cardiovascular stress response to physical exercise may reveal subtle pathology that would have been undetectable at rest in research settings with presumably healthy pediatric populations.…”
Section: Cardiovascular Stress Response To Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Isometric exercise involves the contraction of skeletal muscle without the elongation of the muscle, as such is also called static exercise [103]. This is feasible during CMR by IHG or isometric bicep exercise [104]. IHG exercise comprises the constant squeezing of a lever on a hand dynamometer, generally to a percentage of the subjects maximum force.…”
Section: Isometric Handgrip Stress Cmrmentioning
confidence: 99%
“…Despite the powerful response of this mechanism being observed a decade ago, its hemodynamic mechanisms remain to be fully elucidated. It remains debatable whether the pressor response is due to increases in cardiac output (CO) [5][6][7][8][9], total peripheral resistance (TPR) [10][11][12][13][14] or both [15][16][17][18]. CO changes during IHG is primarily driven by an elevated heart rate (HR), whilst the stroke volume (SV) is slightly reduced due to the tachycardia and increased afterload, or even maintained following both augmented ventricular contractility [19,20] and constant or elevated preload via central blood volume mobilization [21].…”
Section: Introductionmentioning
confidence: 99%